SWOT Analysis in The Implementation Of Electoral Management Policies in Surabaya: A Case Study Approach - Bukhari Bukhari; Ika Devy Pramudiana; Ulul Albab; Widyawati Widyawati; Sri Kamariyah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to evaluate the implementation of electoral policies in Surabaya City using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The main issue faced is the suboptimal application of policies, despite various programs being launched to increase voter participation. SWOT analysis is a tool used to identify strengths, weaknesses, opportunities, and threats within an organization or policy. This research employs a qualitative approach with a case study design, involving in-depth interviews, participant observation, and document analysis to collect data from policymakers, policy implementers, and the general public. The results indicate that the primary strengths lie in competent human resources and capable technological infrastructure, while weaknesses include a lack of inter-agency coordination and budget constraints. Opportunities can be leveraged through technological advancements and community support, whereas threats include regulatory changes and cybersecurity risks. The study provides recommendations to enhance coordination, develop voter training and education programs, and strengthen cybersecurity. Thus, it is hoped that the electoral process in Surabaya will become more effective, efficient, and transparent, gaining full trust from the public.